QR code of coupon college system by using mobile application for Kolej Zamrud & Baiduri, UiTM Puncak Alam / Shah Rezzan Ag Zainal, Mohamad Hassan Mohd Zain and Mohamad Mustaqim Mohamad Zaki - Ag Zainal, Shah Rezzan; Mohd Zain, Mohamad Hassan; Mohamad Zaki, Mohamad Mustaqim (2018)
The current bar code scanning system has several problems arise even though they are an improvement over the event coupon system. The first problem arise is the inefficient way of collecting and processing the data received. Due to the limited number of scanner, this is only one per college, it causing the need to key in the student's matrix number manually when there are too many students attending the events. The recurring way of registering and storing data contributed to the inefficient process. The inefficiency also may cause corrupted or damaged data during both collecting and processing. The second problem arise is the system is time consuming. Using the bar code scanning system, the students would still need to line up in order to register themselves before and after the event. Referring to the problem of limited scanner, the line up would be long as there is only one scanner to scan the matrix card which causes the process to be done slowly. The students also have no mean of referring the events that they have attended. That have been problems occur due the students claimed they have scanned their matrix card but is not successfully registered into the system. In order to refer back the event they have been attended, they will need to physically go to the college information counter and ask the staff to check for them.